FLUID TRANSFER IN HIGH-GRADE METAMORPHIC TERRAINS INTRUDED BY ANOROGENIC GRANITES: THE THOR RANGE, ANTARCTICA - Bucher K.; Frost B.R. (My University, 2006)
A composite intrusive igneous complex in the central mountain range of Queen Maud Land (Thor Range), Antarctica, displays characteristic features of anorogenic granites. A suite of massive intrusives and various sets of dykes and satellite intrusions are ferroan, alkalic to alkali–calcic, and weakly peraluminous. An early set of plutons consists of charnockitic alkali-granites; a later group of plutons comprises fayalite Qtz-syenites. Coarse mesoperthite is the dominant mineral in all rocks, quartz is abundant and plagioclase is a minor mineral. Olivine (fayalite) is the characteristic mafic mineral, but subcalcic augite and occasionally pigeonite or orthopyroxene are present. In most samples, amphibole is the dominant mafic mineral and its composition is close to end-member hastingsite. It contains high concentrations of F and Cl. Some samples contain igneous fluorite. Thermobarometry suggests a temperature of 900 ± 25°C and a pressure of 0·4 ± 0·1?GPa for the crystallization conditions of the pyroxene–olivine assemblages. The solidus temperature of 800–850°C for both suites of plutonic rocks is typical of water-deficient granitic melts. The estimated low water activity of 0·3–0·5 at solidus conditions is consistent with the high halogen content of the bulk-rocks and their constituent minerals. In the absence of an aqueous fluid, the halogens remained in the minerals at the solidus. Oxygen fugacity stayed below QFM in all igneous rocks above solidus. This is typical of melts derived from partial melting of mafic source rocks. The igneous rocks were locally affected by at least three distinct episodes of hydration. As the melt approached solidus conditions, fayalite and pyroxene were locally transformed into hastingsite as a result of increasing fugacity of volatile components. Fayalite-free and fayalite-bearing igneous rocks are arranged in banded structures. Subsolidus hydration locally modified the igneous rocks and transformed pyroxene- and fayalite-bearing granites into biotite-granites and hornblende-granites in which all evidence of former high-T history was erased. This local hydration of igneous rocks occurred in response to uptake of H2O that had been given off by gneissic xenoliths as a result of progressing, continuous, dehydration reactions. The reactions in the gneiss xenoliths were driven by contact metamorphism. This exchange of H2O between igneous and metamorphic rocks occurred in a fluid-absent regime at temperatures of about 750°C. Late reaction veins formed by hydraulic fracturing of the plutonic rocks and indicate the presence of a low-density fluid phase at amphibolite facies conditions.
Keywords: anorogenic granite; fayalite; hastingsite; fluid recycling; Antarctica